2021
DOI: 10.1002/aelm.202100798
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Crystalline Rylenediimides with Highly Order Smectic Layer Structure as a Floating Gate for Multiband Photoresponding Photonic Transistor Memory

Abstract: With the growing demands of light fidelity technology, photonic transistor memory has gained considerable attention for next‐generation optoelectronic devices. In this work, alkylated rylenediimides of 2,9‐diphenethylanthra[2,1,9‐def:6,5,10‐d“e”f]diisoquinoline‐1,3,8,10(2H,9H)‐tetraone (C8‐PDI) and 2,7‐dioctylbenzo[lmn][3,8]phenanthroline‐1,3,6,8(2H,7H)‐tetraone (C8‐NDI), and pyromellitic diimide of 2,6‐dioctylpyrrolo[3,4‐f]isoindole‐1,3,5,7(2H,6H)‐tetraone (C8‐PMDI) have been used as floating gate electrets i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Phototransistor memory with a direct heterojunction design typically requires a gate bias to program and read the device owing to the lack of a charge-blocking medium. , Therefore, organic-molecule-based electrets were tailored using nanostructures to improve their charge storage capability. For example, layer structures with an end-on orientation stabilize the trapped charge in the self-assembled insulated layers. ,,, However, insulated blocking layers with an end-on orientation also form a barrier that hinders carrier tunneling during the photowriting process. Therefore, a face-on orientation is more favorable than an end-on orientation for organic-molecule-based electrets to improve the photoresponse of a memory device.…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Phototransistor memory with a direct heterojunction design typically requires a gate bias to program and read the device owing to the lack of a charge-blocking medium. , Therefore, organic-molecule-based electrets were tailored using nanostructures to improve their charge storage capability. For example, layer structures with an end-on orientation stabilize the trapped charge in the self-assembled insulated layers. ,,, However, insulated blocking layers with an end-on orientation also form a barrier that hinders carrier tunneling during the photowriting process. Therefore, a face-on orientation is more favorable than an end-on orientation for organic-molecule-based electrets to improve the photoresponse of a memory device.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Diverse electret designs have been developed to improve the performance of phototransistor memory, including floating gates, photoactive polymers, and organic molecules. Floating-gate electrets consist of photoactive materials (including perovskite nanocrystals, metal nanoparticles, fluorescent dyes, and quantum dots) dispersed in an insulating polymer matrix. Photoactive polymer electrets are divided into three categories: (i) conjugated/insulated polymer blends; (ii) conjugated block copolymers; and (iii) photoluminescent polymers utilizing aggregation-enhanced emission, aggregation-induced emission, or aggregation-caused quenching effect .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 115 ] In addition to the rod–coil molecules, Lin et al reported the use of rod‐like molecules of alkylated rylenediimides of 2,7‐dioctylbenzo[ lmn ][3,8]phenanthroline‐1,3,6,8(2 H ,7 H )‐tetraone (C8‐NDI) and pyromellitic diimide of 2,6‐dioctylpyrrolo[3,4‐f]isoindole‐1,3,5,7(2 H ,6 H )‐tetraone (C8‐PMDI) as phototransistor memory electrets. [ 116 ] The rylenediimide films were thermally annealed at temperatures above their phase‐transition points to form liquid crystals, and homotropically aligned films were obtained by cooling from the liquid‐crystalline phases. The resulting rylenediimide films with 3D‐ordered smectic layer structures and brickwork stackings constituted effective phototransistor memory electrets, and a memory device obtained by combining them with an n‐type channel of BPE−PDI demonstrated an acceptable memory ratio of 10 5 over 10 4 s.…”
Section: Development Of Phototransistor Memorymentioning
confidence: 99%